How personal values follow the societal lockdown due to COVID-19: Case of business students in Slovenia - Potocan, Vojko; Nedelko, Zlatko (Frontiers in Psychology, 2023)
We examined patterns of change and stability in four higher-order groups of Schwartz values among individuals during societal lockdown caused by COVID-19 epidemic. The study involves comparison of personal values of 85 young adults during societal lockdown, with their personal values in pre- and post-pandemic periods. Sampled group of individual includes undergraduate and graduate students from University of Maribor, Faculty of Economics and Business, Maribor, Slovenia. Contrary to previous publications, our results indicate a decrease of mean-level for all four higher-order groups of individuals' values during societal lockdown of COVID-19. In the value hierarchy, self-transcendence values remain first, followed by conservation, openness to change, and self-enhancement values. In the period after the COVID-19, personal values again approached their pre-pandemic levels. Self-transcendence and conservation returned close to baseline levels, while openness to change and self-enhancement values exceeded initial pre-epidemic levels. In the value hierarchy, leading openness to change values, followed by the self-transcendence, self-enhancement, and conservation values. We discuss perceived changes in young adults’ values due to the COVID-19 pandemic and present their capacities for dealing with potential unfavorable and threatening circumstances in the future.